2015
DOI: 10.5005/jp-journals-10013-1220
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nasal Endoscopy in Sinonasal Diseases

Abstract: Aims and objectives: To evaluate sinunasal diseases with the help of nasal endoscopy. To study efficacy of nasal endoscopy in diagnosing nasal pathology over clinical examination. To define medical and surgical functional endoscopic sinus surgery (FESS), management according to type of nasal pathology. To define applications of nasal endoscopy (biopsy, swab, epistaxis control, foreign body removal, rhinolith removal, follow-up). Materials and methods: Total 100 patients were studied. Patients came with complai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Ritesh Shelkar et al 12 in 2014 evaluated 100 patients of CRS with the help of nasal endoscopy, they are concluded that diagnostic nasal endoscopy is gold standard tool in patients having sinonasal complaints.…”
Section: Original Articlementioning
confidence: 99%
“…Ritesh Shelkar et al 12 in 2014 evaluated 100 patients of CRS with the help of nasal endoscopy, they are concluded that diagnostic nasal endoscopy is gold standard tool in patients having sinonasal complaints.…”
Section: Original Articlementioning
confidence: 99%
“…Sample size of 756 subjects was calculated keeping level of significance (α ) as 0.05, estimated proportion (p) as 0.23 and estimated error (d) as 0.03; where p (estimated proportion) was calculated based on a previous study by Shelkar et al 4 All the data was added in a master chart and was processed using SPSS software (version 22).…”
Section: Sampling and Statisticsmentioning
confidence: 99%
“…This can be attributed to the better visualization of superior part of nasal cavity and the roof with angulation of scopes. Shelkar et al 4 in their study, made 100 of subjects undergo nasal endoscopic examination with 0 & 30 degree scopes. Nasal polyposis was seen in 27%, Mucopus in 22 %, nasal masses in 12%, rhinolith or impacted foreign body in 4 % and CSF rhinorrhoea in 1% study population.…”
Section: Figure 2-2a-bar Graph Representing Distribution Of Age Group...mentioning
confidence: 99%
See 1 more Smart Citation
“…Messerklinger was the first to start endoscopic nasal and paranasal sinus surgery [3]. The use of endoscope during the last decade provided high quality visualization of the intranasal anatomy and improved the knowledge on the intranasal pathology [3,8]. Nasal endoscopy helps to identify the bleeding sources in the nasal cavity that are impossible to be seen by anterior and posterior rhinoscopy.…”
Section: Introductionmentioning
confidence: 99%